Analysis of Budgeting, Administration, and Accountability of Grant Funds in the 2020 Medan Mayor and Deputy Mayor Elections at the Medan City General Election Commission - Wulan, Ira Nawang; Ginting, Bengkel; Ridho, Hatta (Universitas Medan Area, 2025)
The Medan City KPU received a grant of Rp 69,349,289,475 from the Medan City Government to implement the 2020 Medan Mayor and Deputy Mayor Elections. The use of funds must be effective, efficient, economical, and accountable. However, the KPU faces several problems in budgeting, administration, and accountability of funds, such as regulatory changes, limited human resources, and delays in reports from the Ad Hoc Body. This study aims to analyze budget governance and grant accountability. The method used is qualitative descriptive, with data obtained through interviews, documentation studies, and content analysis. The study results show that the Medan City KPU has implemented the budget according to applicable regulations and is transparent in budget planning and procurement of goods and services. However, it is less transparent in providing financial information to the public. The Medan City KPU is also accountable, efficient, and effective in managing the Regional Election budget.